Dynamic gestational week prediction model for pre-eclampsia based on ID3 algorithm - Li, Ziwei; Xu, Qi; Sun, Ge; Jia, Runqing; Yang, Lin; Liu, Guoli; Hao, Dongmei; Zhang, Song; Yang, Yimin; Li, Xuwen; Zhang, Xinyu; Lian, Cuiting (Frontiers in Physiology, 2022)
Pre-eclampsia (PE) is a type of hypertensive disorder during pregnancy, which is a serious threat to the life of mother and fetus. It is a placenta-derived disease that results in placental damage and necrosis due to systemic small vessel spasms that cause pathological changes such as ischemia and hypoxia and oxidative stress, which leads to fetal and maternal damage. In this study, four types of risk factors, namely, clinical epidemiology, hemodynamics, basic biochemistry, and biomarkers, were used for the initial selection of model parameters related to PE, and factors that were easily available and clinically recognized as being associated with a higher risk of PE were selected based on hospital medical record data. The model parameters were then further analyzed and screened in two subgroups: early-onset pre-eclampsia (EOPE) and late-onset pre-eclampsia (LOPE). Dynamic gestational week prediction model for PE using decision tree ID3 algorithm in machine learning. Performance of the model was: macro average (precision=76%, recall=73%, F1-score=75%), weighted average (precision=88%, recall=89%, F1-score=89%) and overall accuracy is 86%. In this study, the addition of the dynamic timeline parameter "gestational week" made the model more convenient for clinical application and achieved effective PE subgroup prediction.